Differences Changes in Cerebellar Functional Connectivity Between Mild Cognitive Impairment and Alzheimer's Disease: A Seed-Based Approach - Tang, Fanyu; Zhu, Donglin; Ma, Wenying; Yao, Qun; Li, Qian; Shi, Jingping (Frontiers in Neurology, 2021)
Background: Recent studies have discovered that functional connections are impaired among patients with Alzheimer's disease (AD), even at the preclinical stage. The cerebellum has been implicated as playing a role in cognitive processes. However, functional connectivity (FC) among cognitive subregions of the cerebellum in patients with AD and amnesic mild cognitive impairment (aMCI) remains to be further elucidated. Objective: Our study aims to investigate the altered FC of the cerebellum among patients with AD and aMCI, compared to healthy controls (HC). Additionally, we explored the role of altered cerebellum FC in the cognitive performance of all subjects. Materials: Resting-state functional magnetic resonance imaging (rs-fMRI) data from three different groups (28 AD patients, 26 aMCI patients and 30 HC) was collected. We defined cerebellar crus II and lobule IX as seed regions to assess the intragroup differences of cortico-cerebellar connectivity. Bias correlational analysis was performed to investigate the relationship between altered FC and neuropsychological performance. Results: Compared to HC, AD patients had decreased FC within the caudate, limbic lobe, medial frontal gyrus (MFG), middle temporal gyrus, superior frontal gyrus, parietal lobe/precuneus, inferior temporal gyrus, and posterior cingulate gyrus. Interestingly, aMCI patients demonstrated increased FC within inferior parietal lobe, and MFG, while they had decreased FC in the thalamus, inferior frontal gyrus, and superior frontal gyrus. Further analysis indicated that altered FC between the left crus II and the right thalamus, as well as between left lobule IX and the right parietal lobe, were both associated with cognitive decline in AD. Disrupted FC between left crus II and right thalamus, as well as between left VIX and right parietal lobe, was associated with attention deficit among subjects with aMCI. Conclusion: These findings indicate that cortico-cerebellar FC in aMCI and AD patients was significantly disrupted with different distributions, particularly in the default mode networks (DMN) and frontal lobe networks (FPN). Increased activity within the frontoparietal areas of aMCI patients indicated a possible compensatory role for the cerebellum in cognitive impairment. Therefore, alterations in the cortico-cerebellar FC represent a novel approach for early diagnosis and a potential therapeutic target for early intervention.